Analysis and Design of a Point of Sales (POS) System at Elite Seven Café & Billiard Kisaran - Cyntha Cyntha; Felicia Yinarta; Kerestina Bulolo; Okta Jaya Harmaja (International Journal of Economics Development Research (IJEDR), 2026)
Efficient sales transaction management is essential for culinary and entertainment businesses such as cafés and billiard venues to ensure fast, accurate, and efficient customer service. However, many businesses still use manual recording systems, which often cause various problems such as delayed recording, transaction calculation errors, and difficulties in preparing sales reports. The development of information technology through a mobile-based Point of Sales (POS) system can serve as a solution because it is able to record transactions automatically, integrate data, and facilitate sales monitoring. Elite Seven Café & Billiard Kisaran still uses manual recording due to employees’ limited understanding of mobile-based Point of Sales (POS) systems. Therefore, this study aims to implement a mobile-based POS system to improve transaction recording efficiency, service speed, and business performance at Elite Seven Café & Billiard Kisaran. This research uses the System Development Life Cycle (SDLC) method with the Waterfall model to implement the mobile-based Point of Sale (POS) system at the business. Data were collected through observation, interviews, and documentation. The system development process includes requirements analysis, system design, implementation, and testing stages. The system implementation results are evaluated to determine their ability to improve transaction efficiency, speed up service, and simplify sales reporting. Based on the results of the study, the implementation of the mobile-based Point of Sales (POS) system at Elite Seven Café & Billiard Kisaran improves the operational performance of the business. This system replaces the less efficient and error-prone manual process. The use of the POS system increases service speed, transaction accuracy, and simplifies data and report management. In addition, employees are able to work more effectively, thereby supporting operational efficiency and enabling more accurate decision-making for the business owner.